Impact of Arab Media Propaganda on Anxiety Levels in Indonesian Society: A Case Study of the Israeli-Palestinian Conflict - Muhammad Imran Nur; Asrining Ghina Maulidia (IQTIDA : Journal of Da'wah and Communication, 2024)
This study examines the geopolitical dynamics in the Arab region, focusing on factors such as regional conflicts, foreign intervention, leadership changes, and control over energy resources. Conflicts like the Syrian war, the Israeli-Palestinian conflict, and tensions in the Persian Gulf significantly shape regional stability. Foreign intervention, whether military or political, often escalates tensions, while leadership transitions and energy resource control, particularly oil, influence regional and global policies. These developments, widely disseminated through digital media, can impact the psychological state of Indonesian society, particularly when propaganda and biased narratives dominate media coverage. This study employs a case study approach combined with content analysis from digital media platforms and anxiety level measurements using psychological instruments such as the State-Trait Anxiety Inventory (STAI), Beck Anxiety Inventory (BAI), and Hamilton Anxiety Rating Scale (HAM-A). Findings reveal that media narratives significantly influence public perception, often amplifying collective anxiety and shaping opinions on geopolitical issues. Digital platforms play a key role in intensifying these effects by merging traditional and modern media channels. The study underscores the importance of media literacy education and public awareness programs to foster critical thinking and resilience against propaganda. These findings provide valuable insights into the intersection of media narratives, public psychology, and geopolitical events, offering recommendations for mitigating their societal impact